Atmospheric air plasma induces increased cell aggregation during the formation of Escherichia coli biofilms - Kwandou, Goldina; Mai-Prochnow, Anne; Prescott, Stuart W.; Spicer, Patrick T.; Cullen, P.J. (Wiley-VCH Verlag, 2018)
Atmospheric air plasma has previously been shown to be a novel and effective method for biofilm eradication. Here we study the effects of plasma on both microbial inactivation and induced structural modification for forming biofilms. New structures are created from aggregates of extracellular polysaccharides and dead bacterial cells, forming a protective and resilient matrix in which the remaining living cells grow and reproduce under proper growth conditions. The new colonies are found to be more resilient in this state, reducing the efficacy of subsequent plasma treatment. We verify that the observed effect is not caused by chemicals produced by plasma reactive species, but instead by the physical processes of drying and convection caused by the plasma discharge.